2015
DOI: 10.1007/s11356-015-4784-0
|View full text |Cite
|
Sign up to set email alerts
|

Solar light (hv) and H2O2/hv photo-disinfection of natural alkaline water (pH 8.6) in a compound parabolic collector at different day periods in Sahelian region

Abstract: The photo-disinfection of natural alkaline surface water (pH 8.6±0.3) for drinking purposes was carried out under solar radiation treatments. The enteric bacteria studied were the wild total coliforms/Escherichia coli (10 4 CFU/ml) and Salmonella spp. (10 4 CFU/ml) naturally present in the water. The photo-disinfection of a 25-l water sample was carried out in a solar compound parabolic collector (CPC) in the absence and in the presence of hydrogen peroxide (H 2 O 2 ). The addition of H 2 O 2 (10 mg/L) to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The action mechanism of microorganism inactivation by UV differs from the pathogen inactivation by UV/H 2 O 2 . When both WW disinfection techniques are compared, the treatment times are shorter when the combined process is applied [53]. Another type of UV radiation is UV-C, which has been demonstrated to be more effective than UVA/TiO 2 or UV/sono-chemical treatments since it has a great disinfectant power, obtaining an inactivation reduction of 6-log in 10 min of treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…The action mechanism of microorganism inactivation by UV differs from the pathogen inactivation by UV/H 2 O 2 . When both WW disinfection techniques are compared, the treatment times are shorter when the combined process is applied [53]. Another type of UV radiation is UV-C, which has been demonstrated to be more effective than UVA/TiO 2 or UV/sono-chemical treatments since it has a great disinfectant power, obtaining an inactivation reduction of 6-log in 10 min of treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…All disinfection studies performed using photo‐Fenton processes with 10 mg H 2 O 2 L −1 have been monitored so far with the standard plate count (SPC) method to quantify the microorganisms . However, SPC is known to only consider cell culturability, neglecting the risk associated with persistence of bacterial viability.…”
Section: Introductionmentioning
confidence: 99%
“…These processes are inhibited by phosphate, sulfate, fluoride, bromide, chloride, carbonate and bicarbonate ions, depending on their concentrations. Inhibition by these species may be due to precipitation of iron, scavenging of ·OH or coordination to dissolve Fe +3 toward forming a less reactive complex . To the best of our knowledge, no study to date has reported on how the presence of anions might affect bacterial cell inactivation by photo‐Fenton at circumneutral pH process in natural well waters.…”
Section: Introductionmentioning
confidence: 99%